The evolution of a conception of citizenly duty towards military service 1854–1914: a study of London press discourse - Piper, A (2012)
This dissertation investigates how personal military service, which during the immensely popular Crimean War of 1854-6 was regarded as the business only of an abstract and lowly soldier-class, had by the eve of the Great War taken on the aspect of a clear and universal citizenly duty in London press discourse. It utilises text-searchable digitised newspaper archives to exhaustively review the whole body of relevant press debate in thirteen key London periodicals, identifying key shifts and trends in press conceptions of civilian military obligation over the six decades between the outbreak of the Crimean War in 1854 and the eve of the Great War in 1914. The analytical narrative that emerges highlights the importance of key events, including the Crimean War, Indian Mutiny, wars of Prussian expansionism, and Boer War, in promoting and shaping the coherent conception of citizenly duty towards military service that would go on to underpin not only the mass enlistments of 1914 but also the acceptance of conscription in 1916. It suggests also the important role of broader cultural and political trends – in particular, the advent of militarist Imperialism, the growing legitimacy of the state, the shift towards a more collectivist ‘social democratic’ liberalism, and the emergence of ‘contractual’ theories of citizenship – in facilitating a reconciliation between the military imperative towards mass civilian military participation and existing liberal values and ideologies. This dissertation reveals that the societal consensus on the duty to enlist in 1914 was by no means a foregone cultural conclusion, nor indeed the relic of an earlier heroic age, but rather the dynamic product of evolution and contestation over six decades. The present study not only provides vital context to our understanding of the ‘rush to the colours’ of 1914, but also represents the first historical investigation of an important and much-neglected aspect of the relationship between war and society.